(untitled) - Kotler, Philip (Englewood Cliffs, N.J., 1996)
The book takes a practical, managerial approach to marketing. It provides a rich depth of practical examples and applications. Each chapter opens with a major example describing an actual company situation. The book gives the marketing student a comprehensive and innovative, managerial and practical introduction to marketing. It also contains dozenz of new photos and advertisements that illustrate key points
Keywords: Marketing